Volatile (H2O, CO2, S, Cl) concentration in magma of the Veiðivötn fissure swarm. A study on melt inclusions in plagioclase, olivine and clinopyroxene - Haraldur Gunnarsson 1964- (2016)
Volatile concentrations in plagioclase, olivine and clinopyroxene hosted melt inclusions and groundmass glasses were analysed from the Bárðarbunga-Veiðivötn volcanic system in the Eastern Volcanic Zone of Iceland. Tephra samples were collected from Brandur, Fontur and Saxi, SE of Þórisvatn. H2O, CO2 concentrations were measured by FTIR and Raman Spectroscopies, while S, Cl, major and minor elements were determined by electron microprobe. The H2O concentration was between 0.08 and 0.53 wt.% and the CO2 concentration was from below detection limit up to 2500 ppm. S concentration varies from 300 ppm to 1700 ppm in groundmass glass and 700 ppm to 1500 ppm in melt inclusions. The relationship between S and other major elements indicate extensive fractional crystallization followed by S degassing. Cl concentration was between 0 and 120 ppm in melt inclusions and between 0 and 250 ppm groundmass glasses. These volatile concentrations are similar to those observed in melt inclusions and groundmass glasses elsewhere in the Eastern Volcanic Zone. Pressure calculated based on melt inclusions revealed a shallow entrapment depth between 0 and 6 km. The pressure calculated from groundmass glass were higher indicating magma storage depth of 3 to 10 km. This suggests that the more evolved melt represented by groundmass glass resided deeper in the crust than the more primitive melt trapped in melt inclusions. Oxygen fugacity was also calculated based on spinel-olivine pairs and yielded log(fO2)FMQ of 1.12 to 1.34, which is significantly higher than values generally assumed for Icelandic primitive melts. Magn rokgjarnra efna í gler innlyksum í plagíóklas, ólivín og klínópýroxen ásamt grunnmassa gleri var ákvarðað í sýnum frá Bárðarbungu-Veiðivatna eldstöðvakerfinu sem er staðsett á eystra gosbeltinu. Gjóskusýnum var safnað frá Brandi, Fonti og Saxa SA af Þórisvatni. H2O og CO2 var mælt með FTIR og Raman litrófsgreiningum, en S og Cl voru mæld með örgreini ásamt almennri efnasamsetningu sýnanna. Magn H2O reyndist vera frá 0.08 ...